Is food produced by farmers healthier, more natural, and gaining more popularity? Research on the influencing mechanism of food producer labels on consumers’ food choices - Zhu, Yong; Jin, Xiaotong (Frontiers in Public Health, 2023)
Introduction Extant studies have demonstrated the relationship between naturalness and healthiness, and the effectiveness of various food labels in influencing consumers’ perception of food and subsequent food choices. However, little attention has been given to food producer labels. Methods Drawing on Stimulation-Organism-Response theory, the current study explored the causal relationship between food producer labels and consumers’ food choices. Three studies (562 participants) were employed to test the main effect, the mediating effect, and the moderating effect. Results The results showed that: (1) food producer label could influence consumers’ food choice, that is, produced-by-farmer label (vs. produced-by-enterprise label vs. control group) could significantly increase consumers’ food choices, while there is no significant difference between produced-by-enterprise label and control group. (2) Perceived naturalness and standardization perception mediate the effects on consumers’ food choices of food producer labels. (3) Food processing level moderates the effect of food producer label on consumers’ food choices. Discussion The current study enriches the research of food label and food choice, expands the application of Stimulation-Organism-Response theory in consumer behavior, and provides some practical suggestions for consumers, enterprise and policy-maker. Various kinds of experiments (online and offline) enhanced the conclusions’ ecological validity. Finally, the limitations and future research are discussed.